Il ruolo delle università nella promozione della mobilità sostenibile e inclusiva - Delponte, Ilaria; Daconto, Luca; Caiello, Simone (SocietàMutamentoPolitica, 2023)
The general understanding of mobility phenomena has increasingly taken on multiple and broad meanings in the various disciplines that question spatial practices and the relationship with the territory by individuals and social groups. The Italian legal system in the sector of urban mobility has recently evolved, introducing new urban planning tools and expanding the sphere of influence and the tasks of the figure of the Mobility Manager. In the promotion and implementation of mobility policies, the University acts as a privileged actor, bringing together very different generations and heterogeneous populations from a socio-economic and cultural point of view as well as in terms of origin and residential contexts; all these are elements which often imply different needs, skills and practices. Within this framework, the paper intends to explore the theme of inclusiveness and disability with special reference to university institutions as preferential places for the collective re-composition of individual beliefs that promote sustainability policies. After the analysis and comparison between international experiences and Italian case studies, the paper concludes with some considerations regarding the still evident critical issues (regulatory, managerial, financial,…) that hinder the implementation of truly effective policies.